KAJIAN PERKEMBANGAN RETRIBUSI PARIWISATA DI KABUPATEN KENDAL (Kajian Kebijakan Perda nomor 10 tahun 2010 tentang Retribusi Jasa Usaha) - Yusuf Rajendra; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Levy of the tourism management under the auspices of the Department of Youth Sport and Tourism of Kendal Regency, and its establishment are arranged in Regional Regulation No. 10 of 2011 of Kendal Regency “the levy of service business in Kendal Regency” which is written in Chapter VII pertaining to the levy of the recreation areas and sports that serve as the legal foundation of an area in Kendal Regency in terms of the handling and management of the Tourism Levy. This research aims to ascertain the development of the levy of the tourism sector in managing three tourist attractions, which are Sendang Sekucing Beach, Curug, Sewu, Boja Swimming Pool as well as to understand the issues faced by Tourism Sector in Kendal Regency in managing the levy. This research is a descriptive research that uses the qualitative approach as the method. Based on the existing types of research, it is acknowledged that there are several issues in regard to the policy of tourism levy, which cover the financial budget funds, addition of the number of the rides or innovation in tourism management, as well as other factors such as human resource in Kendal Regency, which can be seen from the considerably low quality and quantity. The offered solution comprises the government’s action in improving the infrastructure development in many tourist sites being managed by the local government to adequately maintain and enhance the number of human resource in the work environment, regarding both the quality and quantity of the tourist destinations in Kendal Regency that should be well-organized.